1990
DOI: 10.1152/ajpregu.1990.258.3.r569
|View full text |Cite
|
Sign up to set email alerts
|

Model of placental glucose consumption and glucose transfer

Abstract: Net ovine uteroplacental glucose consumption (Ro,up) and transfer rates to the fetus (Rf,up) were measured at different concentrations of maternal (GA) and fetal (Ga) arterial plasma glucose that were set and maintained independently by a glucose clamp procedure. Five GA/Ga combinations were studied: 70/15, 70/20, 70/30, 50/14, and 50/24 mg/dl. Rf,up was inversely related to Ga both at GA = 70 and GA = 50. Linear regression analysis of Rf,up vs. Ga for the GA = 70 and GA = 50 groups of observations revealed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 0 publications
4
60
0
Order By: Relevance
“…The control data for hepatic and umbilical uptakes are in good agreement with previous measurements (3,5,8,12,13,18,23,25). However, this is the first study in which the fetal hepatic uptakes of glucose and all major glucogenic substrates have been measured in the same experimental preparation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The control data for hepatic and umbilical uptakes are in good agreement with previous measurements (3,5,8,12,13,18,23,25). However, this is the first study in which the fetal hepatic uptakes of glucose and all major glucogenic substrates have been measured in the same experimental preparation.…”
Section: Discussionsupporting
confidence: 88%
“…The transport rate of maternal glucose to the fetus is a function of the glucose concentration difference between maternal and fetal plasma (12). We surmise that fetal hepatic glucose production was the main cause of the increase in fetal plasma glucose, which in turn caused a decrease in the transplacental glucose concentration gradient that drives maternal glucose into the umbilical circulation.…”
Section: Discussionmentioning
confidence: 91%
“…Which of these several factors led to the small increase in fetal plasma arginine enrichment in period 2 cannot be determined from the data in this study. Confirmation of these observations will require a more complete experimental approach with bidirectional kinetic analysis of tracers and tracee infused into the mother and the fetus at different maternal and fetal arginine concentrations, similar to our previously published kinetic analysis of placental glucose transfer and metabolism (23).…”
supporting
confidence: 55%
“…The human placental perfusion studies demonstrate that the maternal to fetal glucose gradient is a major determinant of fetal blood glucose concentrations and may be based on polarized glucose transporter concentration differences in the trophoblast. Data from in vivo sheep studies by Hay et al have also shown that the maternal to fetal glucose gradient is the major driving force for fetal glucose concentration [95]. It has also been determined in both sheep and humans that the transplacental glucose gradient is increased near term as a result of decreasing fetal glucose concentrations [96,97].…”
Section: Placental Glucose Transfer and Metabolismmentioning
confidence: 95%